Bos taurus and Bos indicus folicular aspiration and oocytes vitrification at field conditions - Cruz, Fabiano Buss; Martins, Leonardo Tondello; Marinho, Luciana Simões Rafagnin; Forell, Fabiana; Vieira, Arnaldo Diniz; Mezzalira, ALceu (Revista de Ciências Agroveterinárias, 2009)
The aim of this study was to evaluate the viability of cryopreservation of bovine oocytes from Bos taurus and Bos indicus cows, at field conditions. The average rate of oocyte recovered by Ovum Pick up (OPU) from Bos taurus taurus cows (Devon) or Bos taurus indicus cows (Nelore), and the embryo development after vitrification were determined. After 60 sessions, an average rate of 4.6 oocytes/session was obtained from Devon cows. This number was significantly lower than the 16.3 oocytes obtained from Nelore cows, in 12 sessions. Selected recovered oocytes were vitrified in 20% EG + 20% DMSO + 0.5 M sucrose, in TCM 199 medium, with open pulled straws (OPS) technology, and stored in a cryogenic container. Just after warmed, oocytes were submitted to standard in vitro maturation, fertilization and culture in the laboratory. There were no differences in cleavage rates obtained from Devon cows oocytes (17.6%) and Nelore cows oocytes (29.1%). Evaluation of embryo development resulted in only one blastocyst obtained from Devon cows. Data from this study showed that Bos taurus indicus cows had higher oocytes recovery rates when compared with Bos taurus taurus, and that association of OPU with oocytes vitrification at farm conditions resulted in unsatisfactory indexes of embryo development, regardless of cow breed.